2017
DOI: 10.1371/journal.pone.0183895
|View full text |Cite|
|
Sign up to set email alerts
|

Enhancing antibacterial effect of sodium hypochlorite by low electric current-assisted sonic agitation

Abstract: BackgroundThis research focused on the effects of low electric current (μE)-assisted sonic agitation of sodium hypochlorite on Enterococcus faecalis infected human root dentin.MethodsExtracted human canine roots were instrumented, sterilized, and experimentally contaminated with E. faecalis. After incubation for 21 days, the presence of the biofilm was confirmed by scanning electron microscopy (n = 3). Roots were randomly divided into seven groups according to decontamination procedures: G1: no treatment; G2: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…These differences are likely explained by study methodologies. In the present study, a higher energy level (80 mA) than in the previous study 38 was used, moreover, a higher concentration of NaOCl (6% NaOCl) than in the previous study 38 was also applied. It stands to reason, that with the high potential for shear forces in such straight and wide canals, as well as higher concentrations of NaOCl being used, even a 2-week-old biofilm would be eradicated.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…These differences are likely explained by study methodologies. In the present study, a higher energy level (80 mA) than in the previous study 38 was used, moreover, a higher concentration of NaOCl (6% NaOCl) than in the previous study 38 was also applied. It stands to reason, that with the high potential for shear forces in such straight and wide canals, as well as higher concentrations of NaOCl being used, even a 2-week-old biofilm would be eradicated.…”
Section: Discussionmentioning
confidence: 85%
“…Other studies have found 2.5% NaOCl incapable of eradicating E. faecalis biofilms with as much as 40 min of contact time 37 . The combination of micro-electric assisted sonic agitation on 5.25% NaOCl was not capable to eradicate 21-day-old E. faecalis biofilms at 10 mA energy level in 60 s 38 . These differences are likely explained by study methodologies.…”
Section: Discussionmentioning
confidence: 91%
“…According to the reviewed articles, potential double origins, lab-adapted strains [ 15 , 16 , 18 , 19 , 20 , 21 , 24 , 26 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] and clinically isolated E. faecalis were noted [ 25 ]. Types of E. faecalis strains which are most widely used by different authors and bacteria origin are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…[ 1,2 ] ClO − plays an essential role in various physiological and pathological processes, including preventing infection and destroying pathogens. [ 3–5 ] Therefore, abnormal ClO − concentration levels can lead to oxidative stress, tissue lesion, and many relative risks related to immune deficiency, myocardial injury, nerve damage, kidney disease, cardiovascular disease, and tumours. [ 6–11 ] Therefore, designing and developing efficient, as well as convenient, monitoring methods that can detect ClO − is significant.…”
Section: Introductionmentioning
confidence: 99%